2011
DOI: 10.1007/s11746-011-1840-x
|View full text |Cite
|
Sign up to set email alerts
|

Oil Content and Fatty Acid Profile of Spanish Cultivars During Olive Fruit Ripening

Abstract: The oils produced from five olive cultivars (i.e. arbequina, gordal, manzanilla, picual and picudo) and the evolution of fatty acid profile during olive fruit ripening were studied. The total oil content increased throughout ripening for Picudo cultivars; however, all other cultivars reached maximum oil contents between ripeness stage 2 and 4. The content of trans (0.3-5.8%), saturated (8.3-21.4%), monounsaturated (41.9-84.1%) and polyunsaturated fatty acids (2.3-49.7%) varied with the ripeness state and culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
5
25
0
Order By: Relevance
“…Olive samples grown from two growing areas were handpicked from the end of September 2011 to January 2012 depending on the earliness of each cv in the ripening stages 4 and 5 (according to the external color of the drupe: 1, green; 2, green–yellow; 3, yellow–purple; 4, purple; and 5, black ) and transported to the laboratory and kept at 4°C. The areas were selected based on their climatic characteristics: Gorgan, which is a damp area in the Northern Caspian (36 51 N, 54 16 E) lowland (13.3 m) and somewhat similar in climate to the Mediterranean one with high humidity (70%) and rainfall (601.0 mm/year), was at one extreme and Qom, as a dry and hot area in the central (34 42 N, 50 51 E) highland (877.4 m) with its climates varying between desert and semi‐desert as well as low humidity (41%) and deficient rainfall (151.1 mm/year), was at the other extreme.…”
Section: Moisture Oil Content and Oxidative Stability Of The Studiementioning
confidence: 99%
“…Olive samples grown from two growing areas were handpicked from the end of September 2011 to January 2012 depending on the earliness of each cv in the ripening stages 4 and 5 (according to the external color of the drupe: 1, green; 2, green–yellow; 3, yellow–purple; 4, purple; and 5, black ) and transported to the laboratory and kept at 4°C. The areas were selected based on their climatic characteristics: Gorgan, which is a damp area in the Northern Caspian (36 51 N, 54 16 E) lowland (13.3 m) and somewhat similar in climate to the Mediterranean one with high humidity (70%) and rainfall (601.0 mm/year), was at one extreme and Qom, as a dry and hot area in the central (34 42 N, 50 51 E) highland (877.4 m) with its climates varying between desert and semi‐desert as well as low humidity (41%) and deficient rainfall (151.1 mm/year), was at the other extreme.…”
Section: Moisture Oil Content and Oxidative Stability Of The Studiementioning
confidence: 99%
“…Having been specified by the International Olive Council (IOC) and the Commission of the European Communities (EEC), the quality of olive oil is determined on the basis of parameters including free fatty acid (FFA) content, peroxide value (PV), UV absorbency, and other quality parameters such as fatty acid profile and total unsaponifiable matter, of which sterols are the main constituents [2]. The fatty acid profile of olive oil has been used not only for characterization and quality evaluation but also for identification of the growing area [3]. Specific profiles of sterols in each oily fruit are also used to detect adulterations or to check the genuineness of the olive oil, as it can be considered a distinct ''fingerprint'' [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The content of saturated, monounsaturated and polyunsaturated fatty acids vary with ripeness and cultivar [3][4][5][6]. However, Gómez-González et al [7] found no significant differences in the fatty acid profiles of the oils when olives were collected with a ripening index (RI) value between two and four [8].…”
Section: Introductionmentioning
confidence: 99%